Republic of Guinea Overcoming Growth Stagnation to Reduce Poverty : Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2018)
Guinea is a country with a rich historical legacy, abundant natural resources, a privileged geographical location - and a rapidly growing population. A successful political transition and the emergence of a vibrant civil society have helped to ensure ethnic peace and the absence of civil wars in the middle of a rather conflict-ridden region. The country faces severe challenges in translating its assets and opportunities into higher incomes for its citizenry. Economic growth has been too weak and volatile to contribute to poverty reduction on a sustained basis. This systematic country diagnostic (SCD) posits that two critical factors have affected Guinea’s development path since its independence in 1958. First, the country endured two long-lived authoritarian regimes and political instability before the inception of democracy in 2010. Such a legacy of attendant poor economic governance led to mismanagement of natural resources, institutional fragmentation of the government, a weak social contract and rule of law, and low and ineffective public investment. Second, the structure of the economy remains dependent on the primary sectors - agriculture and mining - lacking diversification in its sources of growth.